ROLE OF PATHYA-APATHYA AND YOGIC PROCEDURES IN THE MANAGEMENT OF COPD (International Journal of Ayurveda and Pharma Research, 2018)
Chronic Obstructive Pulmonary Disease (COPD) is a chronic lung disease that is often preventable and treatable. In Ayurvedic texts Shwasa Roga has been described having symptomatology close to COPD. COPD damages the airways in lungs and leads to shortness of breath, impacting patient`s work, exercise, sleep and other everyday activities. More than 11 million people in the U. S. suffer from COPD and its prevalence has been increasing steadily over the past 20 years. It causes serious long-term disability and early death. COPD includes both chronic bronchitis and emphysema. Risk factor includes exposure to air pollution, second-hand smoke and occupational dusts and chemicals, smoking, cold weather etc. which are also mentioned in Ayurvedic classics. Identification, reduction and control of risk factors to prevent the onset of COPD are important steps towards developing strategies for prevention of COPD. The aims and objectives of Ayurveda are to maintain the health of a healthy person and to cure the diseases of the patients. It is signifies that “prevention is better than cure.” To maintain the health, Ayurveda laid many basic principles like Ritucharya (seasonal regime), Dincharya (diumal regime) etc. The Yogic procedures and the concept of Pathya (wholesome) and Apathya (unwholesome) is the peculiarity of Ayurveda for the management of COPD and the treatment module includes- Panchakarma (Vamana, Virechana, Dhumapana and Nasya), external therapies (Lepas, Dhara, Sthanika Abhayanga and Swedana) and internal medications are very effective in COPD.